2008
DOI: 10.1016/j.bbrc.2008.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of human tissue-specific differences in methylation

Abstract: Tissue-specific differentially methylated regions (tDMRs) have been identified and implicated for their indispensable involvement in mammalian development and tissue differentiation. In this report, a quantitative DNA methylation analysis was performed for 13 human orthologous regions of recently confirmed mouse tDMRs by using Sequenom Mass Array, by which bisulfite-treated fragments are quantitatively detected using time of flight masspectroscopy analysis. Eight regions were shown as tDMRs in various tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…DNA methylation patterns are susceptible to change in response to environmental stimuli such as diet or stress, and are most vulnerable to a change during early in utero development. Once DNA methylation patterns are established through cellular differentiation, however, they display a limited dynamic range in normal conditions, giving various cells and tissues a unique cell-or tissuespecific DNA methylation profile [17][18][19][20][21]. Genome-wide analysis of DNA methylation also indicates that numerous tissue-specific differentially methylated regions (tDMRs) exist in the mammalian genome [22][23][24].…”
Section: Introductionmentioning
confidence: 97%
“…DNA methylation patterns are susceptible to change in response to environmental stimuli such as diet or stress, and are most vulnerable to a change during early in utero development. Once DNA methylation patterns are established through cellular differentiation, however, they display a limited dynamic range in normal conditions, giving various cells and tissues a unique cell-or tissuespecific DNA methylation profile [17][18][19][20][21]. Genome-wide analysis of DNA methylation also indicates that numerous tissue-specific differentially methylated regions (tDMRs) exist in the mammalian genome [22][23][24].…”
Section: Introductionmentioning
confidence: 97%
“…Some CpG loci have been reported that are related to cell differentiation [11][12][13], allowing them to be used in identifying the specific cell or tissue types through their methylation status; this also provides opportunities for identification of biofluids for forensic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…(D) Methylation map compiling all methylation data sorted manually by CpG observed/expected. (EG) Tissue clusterings showing the similarity between the methylation patterns of tissues obtained by reduced representation bisulfite sequencing from 17 mouse cell types compiled in 9114 regions of interest (14) (E) by quantitative MALDI-TOF methylation analysis (13) (F) or by meDIP (11) (G).…”
mentioning
confidence: 99%
“…These data were analyzed with BiQ Analyzer and processed by BDPC. Additionally, to show the usability of the new BDPC module, we processed published DNA methylation data determined using the Sequenom Mass Array (13) and data generated by deep sequencing techniques (14). …”
mentioning
confidence: 99%